Summary of the research The effect of a training curriculum according to the air energy system With training loads of varying intensity and size in developing the cardiac functional capacity of the young free wrestlers - Shuaib, Jamal Mohammad; Judy, Suzan Khalifa; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The research aimed to prepre a training curriculum according to the pneumatic power system With training loads of varying intensity and size for young freestyle wrestling players, as well as learning about the impact of the training curriculum according to the aerobic energy system With training loads of varying intensity and size in developing the functional capacity of the heart for young freestyle wrestling players, as the researchers used the experimental approach to its suitability to solve the research problem and the design of the two equivalent groups with pre and post tests were chosen randomly, as the research sample consisted of young wrestling players in Diyala Province with the weight category (60 - 66 ) kg (12) wrestlers out of (22) wrestlers, and by lot they were randomly divided into two experimental and control groups, each group (6) wrestlers and each weight (3) wrestlers, as numbers (1,2,3, 7, 8, 9) were randomly drawn wrestlers weighing (60) kg, and the numbers (4, 5, 6, 10, 11, 12) were also randomly drawn by wrestlers at weight (66) kg, so the numbers represented (1 - 6) The experimental group and the numbers (7-12) represented the control group, in addition to using the appropriate means, tools and devices, and the exploratory experiment was conducted, as well as conducting tribal tests for the two groups, and applying the training curriculum, Then conducting dimensional tests for the two groups, after that the data were emptied and statistically processed, and then presented, analyzed and discussed, and the researchers reached several conclusions, which are : The training curriculum prepared by the researchers contributed greatly to the dvelopment of the cardiac functional ability of the members of the experimental group . The training curriculum prepared by the researchers clearly contributed to the occurrence of the functional condition of the heart by decreasing the pulse rate at rest time for the members of the experimental group. The experimental group had an advantage over the control group in developing a cardiac functional ability.